1999
DOI: 10.1046/j.1365-2249.1999.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic risk factors for anti-neutrophil cytoplasmic antibody (ANCA)-associated systemic vasculitis

Abstract: Wegener's granulomatosis (WG) and microscopic polyangiitis are systemic autoimmune diseases characterized by the presence of ANCA in the sera of patients. Little is known about the aetiologic factors and genetic predisposition as well as the pathogenesis of these disease entities. A slightly decreased representation of HLA-DRB1*13 and HLA-DQB1*0603 individuals was observed in our cohort of ANCA-associated systemic vasculitis (AASV) patients compared with controls. In addition, HLA-DRB1*04 individuals were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 43 publications
0
31
1
Order By: Relevance
“…ANCA antigens are mainly located in azurophilic granules of polymorphonuclear granulocytes; after being primed by TNFa, there are more ANCA antigens expressed on the membrane of polymorphonuclear granulocytes (29,30). Over-representation of TNFa 2a/DRB1*04 might contribute to the severe courses of GPA (11). We speculated that the mechanism of HLA-DRB1*0405 contributing to the outcome of AAV is possibly through the over-representation of TNFa, resulting in poor prognosis of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…ANCA antigens are mainly located in azurophilic granules of polymorphonuclear granulocytes; after being primed by TNFa, there are more ANCA antigens expressed on the membrane of polymorphonuclear granulocytes (29,30). Over-representation of TNFa 2a/DRB1*04 might contribute to the severe courses of GPA (11). We speculated that the mechanism of HLA-DRB1*0405 contributing to the outcome of AAV is possibly through the over-representation of TNFa, resulting in poor prognosis of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the etiology of AAV is poorly understood, substantial difference in the incidence among populations 2 and sporadic reports of multiplex families 3 suggest a role of genetic predisposition. With respect to MPO-ANCA associated vasculitis, previous studies reported association of HLA [4][5][6] and non-HLA genes, 7-10 although many of them have not been confirmed by independent studies.…”
Section: Introductionmentioning
confidence: 99%
“…36 However, it has been shown to be nonsignificant in many other inflammatory diseases. [37][38][39] Our study also, could not find any association of TNF-α -308 gene polymorphism with diabetic peripheral neuropathy. Similarly, a study in South Indian population also could not find any association of TNF-α with diabetic peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 50%